Fractures of the coracoid process - pathoanatomy and classification: based on thirty nine cases with three dimensional computerised tomography reconstructions - Bartoníček, Jan; Tuček, Michal; Strnad, Tomáš; Naňka, Ondřej (International orthopaedics, 2021)
PURPOSE: Until now, classifications of coracoid fractures have been based on plain radiographs, without use of 3D CT reconstructions. Therefore, the aim of the present study has been to describe the pathoanatomy of these fractures and their associated injuries to the shoulder girdle, on the basis of 3D CT reconstructions. METHODS: The cohort comprised 39 patients, who each sustained a coracoid fracture investigated with 3D CT reconstructions. The patients were assessed in terms of age, gender, pathoanatomy of the coracoid fracture, fractures of other parts of the scapula, and associated injuries to the shoulder girdle. RESULTS: We identified 24 fractures of the base, one fracture of the beak body, eight fractures of the apex, and six comminuted fractures of the coracoid process. A total of 22 associated injuries were found (7 fractures of the acromion, 5 fractures of the anterior glenoid rim, 3 fractures of the superior glenoid, 1 fracture of the inferior glenoid, 4 fractures of the surgical neck, 2 fractures of the scapular body) and 18 other associated injuries to the shoulder girdle (8 AC dislocations, 5 proximal humeral fractures, and 5 clavicular fractures). CONCLUSION: On the basis of 3D CT reconstructions, four basic coracoid fracture patterns were identified. The authors´ findings and literature review have shown that a considerable number of coracoid fractures are combined with injuries to other parts of scapula and shoulder girdle. These associated injuries must be taken into account and targeted when taking the patient's history, and during clinical and primarily radiological examinations.
Keywords: fraktury kostí; Clavicle; Humans; Coracoid Process; lidé; Scapula; processus coracoideus; Fractures, Bone; Acromion; akromion; klíční kost; lopatka; Tomography, X-Ray Computed; počítačová rentgenová tomografie